Perbandingan Teknik Klasifikasi Untuk Memprediksi Kualitas Kinerja Karyawan - Hijrah Hijrah; Mukhlizar Mukhlizar; T.M. Aziz Pandria (Universitas Teuku Umar, 2020)
This study was conducted to compare several classification techniques used to determine the quality of employee performance. the quality of employee performance is very influential on the development of a company, there are many attributes that are used as a measure of employee performance the more attributes used then the better the results of the quality of assessment performed. to get maximum result hence done by comparison of technique of classification, comparison done by seeing result of performance of method used. method used by algorithm C4.5, Naive Bayes, and k-nearest neighbors, method to be used will be tested using tool rapid miner.